O American Israel Public Affairs Committee (AIPAC) e sua influencia na politica externa dos Estados Unidos - Pinto, Lucas Vasconcelos (2015)
This work has as its theme the influence of The American Israel Public Affairs Committee AIPAC in the foreign policy of the United States US. Firstly it was systematized a state of the art on the subject based on two main lines of thought: one of John Mearsheimer and Stephen walt and another of Noam Chomsky Gilbert Achcar and Norman Finkelstein. While those ones highlight the power of the so called Pro-Israel lobby - from which AIPAC is the most structured and renowned organization - in US politics those second ones point out that the helm of US foreign policy toward Israel is its own national interest not the Lobby. Secondly it was aimed a historical survey about AIPAC and an analysis of its structure and its procedures. It was founded then that AIPAC - as a lobbying organization an interest group - according to the law cannot make financial contributions directly to politicians. It was founded however that this practice may occur indirectly through at least two ways: through its own members contributing individually and/or by Political Action Committees PACs - institutions created specifically to this end of raising funds to political campaigns in order to elect and defeat candidates or even to influence those who are already in the Government. And thirdly it was sought to synthesize the state of the art to the historical and structural study on AIPAC. Based on the dialogue of the two main theoretical visions worked - under a optic of complementarity rather than of exclusion - alongside with an examination of AIPAC s action in history this study led us to infer that AIPAC which was founded in 1959 in the Cold War context remains being influential in US politics even with the change in the international system at the end of the Cold War.